Searching for the best post-land abandonment management to enhance long-term carbon storage in Mediterranean mountain areas - Melani Cortijos-López; Teodoro Lasanta; Erik Cammeraat; Estela Nadal-Romero (Geography and Sustainability)
The abandonment of rural activities in the Mediterranean mid-mountains has led to the activation of revegetation processes, as well as the subsequent implementation of various management measures to mitigate the associated ecosystem disservices. Focusing on soil environment and its growing importance in a climate change scenario, it is of great interest to study how land management and landscape changes can affect, not only the soil carbon storage process, but also its dynamics. A study was conducted in La Rioja (Iberian System, Spain), comparing three post-abandonment management strategies: secondary succession, forest management, and shrub clearing and extensive grazing. These strategies were analysed in two types of soil environments (acid and alkaline) and for two depth ranges (0–20 cm and 20–40 cm). Laboratory analyses were performed on aggregate stability and soil organic carbon fractionation with regard to three aggregate sizes (< 2 mm, 2–5 mm, > 5 mm) and three density fractions (free labile, occluded, and heavy fraction). The results showed that: 1) SOC content in aggregates < 2 mm (relative to total SOC) increases with shrub clearing and grazing strategy in acid environments; 2) aggregate stability benefits from the implementation of afforestation in acid environments and from all three study strategies in alkaline ones; 3) in acid environments, the percentage of labile fractions (free and occluded) in afforested sites is significantly higher compared with shrubland, while in alkaline environments, recalcitrant SOC is significantly higher in shrub clearing sites. Thus, land management should be focused on SOC storage after land abandonment in Mediterranean mountainous environments.